Lifetime reproductive efficiency of BALB/c mouse pairs after an environmental modification at 3 mating ages - Moreira, Virginia B. [UNESP]; Mattaraia, Vania G. M.; Moura, Ana Silvia A. M. T. [UNESP] (Amer Assoc Laboratory Animal Science, 2015)
The aim of this study was to evaluate the effects of an environment change and the age at which mating pairs were formed on the lifetime reproductive performance of BALB/c mice. We assigned 60 monogamous pairs to a randomized design in a 2 x 3 factorial arrangement (with or without an environmental modification and with 3 mating ages: 28, 45, or 60 d). Autoclaved cardboard tubes (length, 10 cm; diameter, 4 cm) were used as the environmental modification. Data were collected from a total of 456 litters over a period of 10 mo. The mice tore the cardboard tube and used its parts both as shelters and as nesting material. The presence of a cardboard tube decreased the preweaning litter mortality rate in the first 6 reproductive cycles. Mating at 28 or 45 d of age also decreased the preweaning mortality rate in the first 6 reproductive cycles, compared with monogamous pairs formed at 60 d of age. Treatments did not affect age at first parturition, number of litters, time between litters, or litter size and weight at birth and weaning. In addition to contributing to animal wellbeing, providing a cardboard tube improved productivity by decreasing the preweaning mortality rate. BALB/c siblings should be paired for mating when no older than 28 d, to reduce preweaning mortality of the offspring.